Pengembangan Multimedia untuk Meningkatkan Pemahaman SKI di Madrasah: Sebuah Kajian Literatur - Seillariski, Ishlah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study explores the role of multimedia in enhancing students’ understanding of Islamic Cultural History (SKI) in madrasahs through a systematic literature review. SKI, as a subject mandated by the curriculum, is often taught in monotonous ways that rely heavily on rote memorization and note-taking, leading to student passivity and disengagement. To address this challenge, the study analyzes how multimedia can provide alternative approaches that are more interactive, student-centered, and motivating. A qualitative literature review was conducted by examining 45,726 sources from ResearchGate, Google Scholar, and Google Search, with inclusion and exclusion criteria applied based on publication year, keywords, type of publication, and topic relevance. From this process, four representative data sets were identified and analyzed. The findings reveal that multimedia significantly improves the learning outcomes of SKI by increasing student-teacher interaction, stimulating motivation, and enabling effective knowledge transfer. Multimedia also supports independent exploration and fosters active learning experiences. Beyond pedagogical benefits, the study highlights psychological implications, such as enhancing emotional and spiritual engagement through audiovisual content, and moral implications, where multimedia can reinforce Islamic values like honesty, responsibility, and the love of knowledge when designed with strong value orientation. In conclusion, the integration of multimedia into SKI teaching is not only a strategy to improve comprehension and engagement but also a medium to cultivate Islamic character and values, provided that its development is carefully adapted to students’ learning needs.